Modulatory role of rutin on 2, 5-hexanedione-induced chromosomal and DNA damage in rats: validation of computational predictions. (3rd March 2020) - Muhammad, Aliyu; Arthur, David Ebuka; Babangida, Sanusi; Erukainure, Ochuko L.; Malami, Ibrahim; Sani, Hadiza; Abdulhamid, Aliyu Waziri; Ajiboye, Idayat Omoyemi; Saka, Ahmed Ariyo; Hamza, Nafisa Muhammed; Asema, Suleiman; Ado, Zaharaddeen Muhammad; et al.
Abstract: The aim of this study was to evaluate the potentials of rutin on 2, 5-hexanedione-induced toxicities. Two successive phases were involved using in silico and in vivo approaches. The in silico was adopted for potential oral toxicity and docking. The in vivo was carried-out in two stages for two weeks; the ameliorative (stage 1, first week), preventive, and curative studies (stage 2, extended to second week). In stage 1, rats were divided into four groups of seven each (distilled water, 3% (v/v) 2, 5-hexanedione, 10 mg/kg rutin, and co-administration). In stage 2, the experimental groups were given either rutin or 2, 5-hexanedione and treated in reverse order. Lipid peroxidation, protein carbonyl, and DNA fragmentation in tissues and bone marrow cells micronucleus were determined. The predicted Median lethal dose (LD50 ) of >5000 mg/kg and toxicity class of five (5) indicates the safety of rutin when orally administered. 2, 5-Hexanedione comfortably docked in to the active sites of SOD (−22.857Kcal/mol; KI = 0.9621 µM), GPx (−11.2032Kcal/mol; KI = 0.9813 µM), and CAT (−16.446Kcal/mol; KI = 0.9726 µM) with strong hydrogen bond and hydrophobic interactions. However, only strong hydrophobic interaction was observed in the case of DNA (−3.3296Kcal/mol; KI = 0.9944). In vivo findings revealed deleterious effects of 2, 5-hexanedione through induction of oxidative and chromosomal/DNA damage characterized by higher level of malondialdehyde, micronuclei formations, and DNA fragmentation. These have invariably, validates the findings from in silico experiments. Furthermore, rutin was able to ameliorate, protect, and reverse these effects, and was relatively non-toxic corroborating toxicity predictions. Rutin exhibited counteractive effects on 2, 5-hexanedione-induced oxidative, chromosomal, and DNA damage.